Cryptographic Attack On LUC-type Cryptosystems Using GMITM (Type 1) - I.N. Sarbini; T.J. Wong; M. Othman; L.F. Koo; A.F.N. Rasedee; P.H. Yiu; F.H. Naning (Institute of Advanced Scientific Research, 2024)
Volume:11 Issue: 12